The principles of designing an expert system in teaching mathematics - Alfarsi G.; Hidayah S.; Tawafak R.M.; Malik S.I.; Jabbar J.; Eldaw A.; Alsidiri A. (American Institute of Physics Inc., 2023)
This examination uncovers general instructional ideas of the Expert Systems (ES) advancement process in the instructive territory. The verification of idea depends on the case of encouraging the eighth grade Algebra subject. The principle commitment in this work is the usage of inventive methodologies in investigation and preparing of information by master framework just as the improvement of the bit by bit calculation to fabricate a table of conditions between subjects in a course, known as Concept-Effect Relationship (CER) model, which is presented in this examination work. The CER model is the center segment of the ES, in light of which the framework constructs the individual instructive system for an understudy. The issue of building a table of conditions between subjects in a course has been a critical deterrent when utilizing this methodology, all things considered, because of its time intricacy and an interest for huge endeavors from numerous specialists. Our epic methodology presents a general calculation for building a reliance table with no connecting to a particular subject, in this manner making CER model usage simpler, all things considered, instructive practice. 2021 American Institute of Physics Inc.. All rights reserved.